Genetic Diversity Analyses of Bread Wheat (Triticum aestivum L.) Genotypes using Microsatellite Markers: Genetic Diversity in Bread Wheat using SSR Markers - Nelwadker, Rahul R; Rouf Mir, Reyazul; Kumar, Satish; Khan, Mohammad Anwar (Journal of Cereal Research, 2025)
Genetic diversity studies of germplasm form the basis of genetic improvement in crop plants. Around 900 wheat germplasm lines collected from different national and international germplasm repositories were subjected to repeated cycles of selection for earliness, yellow rust resistance and other agronomic traits over five years under research programme of department and under a University Grant Commission funded research project to ultimately constitute a set 26 most promising candidate genotypes. These twenty six wheat germplasm lines were studied for genetic diversity using forty-two previously developed microsatellite markers. The study revealed the overall size of PCR products amplified ranged from 100-330 bp, highest polymorphic information content (PIC) value of 0.67 for Xgwm120 while lowest value of 0.19 was observed for Xgwm155 with an overall average of 0.48. For gene diversity, lowest value of 0.22 was observed for Xgwm155 while highest value of 0.72 was observed for Xgwm120 with an overall average of 0.56. The cluster analysis based on molecular analysis of twenty-six selected genotypes revealed that genotypes WS-25 and WS-6 were found most diverse genotypes with dissimilarity index of 0.724 and the genotypes WS-15 and WS-17 were reported to be similar with 0.209 dissimilarity index value. The dendrogram generated using molecular data of polymorphic markers grouped 26 wheat genotypes into 3 distinct main clusters and 10 sub clusters. The understanding of these diverse genotypes can be helpful for selection of parental lines to breed for important agronomic traits.